Assessing the potential of laboratory instructional tool through Synthesia AI: a case study on student learning outcome / Jacqueline Joseph - Joseph, Jacqueline (UiTM Press, 2023)
This research study aims to investigate the effectiveness of utilizing Synthesia Artificial Intelligence (AI), an advanced instructional tool, in enhancing laboratory experiments. The research focused on evaluating the impact of incorporating Synthesia AI as a supplementary learning resource on student learning outcomes in laboratory settings. Synthesia AI is a cutting-edge technology that revolutionizes students' immersive learning experience. With its advanced machine learning algorithms, Synthesia AI can generate photorealistic video content featuring virtual actors and presenters that can be programmed to speak in multiple languages, accents, and even emotional tones. In this study, an instructional-based laboratory experiment was conducted using Synthesia AI. The participants were from the Sabah Branch of UiTM, and enrolled in a Basic Plant Science laboratory course under the Pre-Diploma Agrotechnology programme. The course was divided into two groups, an experimental group and a control group. The experimental group received laboratory instructions through Synthesia AI videos, while the control group received traditional laboratory instructions